P222 Short And Long-term Consequences Of Pneumothorax Following Ct-guided Lung Biopsy For Lung Malignancy. (10th November 2014) - Johnson, E; MacKenzie, A; Tsim, S; Blyth, KG
Abstract : Introduction and objectives: Pneumothorax (PTX) is a common complication of Computed Tomography-guided lung biopsy (CTLB). We sought to quantify the short and long-term consequences of post-CTLB PTX in patients with lung malignancy. Methods: We retrospectively reviewed case records and imaging of all who underwent CTLB in NHS Greater Glasgow and Clyde between August 2011 and August 2012. Patient characteristics (including diagnosis, lung function and blood results), biopsy characteristics, 30-day mortality, PTX management and survival were recorded. Lesion size, depth and maximum PTX depth were directly measured on digitally-stored PACS images. Patients were classified into no PTX, non-significant PTX (nsPTX) and significant PTX (sPTX), which was defined as any PTX which required pleural intervention. Differences in patient and biopsy characteristics between groups were identified by ANOVA and quantified by Tukey's Multiple Comparisons Test. Kaplan-Meier curves were plotted and differences quantified by log-rank, log-rank for trend and Hazard Ratios. Results are mean (±SD). Results: 324 CTLB were performed. Malignancy was confirmed in 285/324 (88%). Mean age was 70(±11) years. 84/285 (29%) developed a PTX. 17/285 (6%) developed a sPTX. There were no deaths related to CTGLB (30-day mortality: 100% in all groups). SPTX were larger than nsPTX (34(±6) mm vs. 19(±6) mm, p = 0.0003). Other factors associated with sPTX were lesion size and depth (see Figure 1 (a and b)), larger needle gauge (p < 0.0001), higher FEV1 (p = 0.01) and lower DLco (p = 0.049). Length of stay (LoS) was longer in sPTX (5.8(±5.9) days, p < 0.0001) and nsPTX (1.7(±2.3) days, p < 0.0001) than No PTX (0.7(±0.9) days), but long-term survival was better (see Figure 1 (c and d)). This survival difference was pronounced in a sub-group of patients with a peripheral non-small cell lung cancer (defined as a lesion depth ≤ 0 mm, n = 53). Conclusions: CTGLB was associated with a low rate of sPTX (6%) and no short-term mortality. sPTX was associated with lung function indicative of emphysema and smaller, deeper lesions. The latter association likely explains the apparent survival advantage found in PTX patients but any long-term survival disadvantage seems unlikely. Post-CTLB PTX may be a positive sign in peripheral NSCLC, possibly inferring resectablilty.